Communication Satisfaction: A Study on Junior Executives working in Private Sector of Bangladesh - Alam, Akhund A Shamsul (Journal of Business and Technology (Dhaka), 2017)
The study was an attempt to explore the level of communication satisfaction perceived by junior executives working in private sector in Bangladesh. Data were collected using the Communication Satisfaction Questionnaire developed by Downs and Hazens (1977). The Questionnaire consisted of 40 items divided into eight dimensions: Communication Climate, Supervisory Communication, Organizational Integration, Media Quality, Co-worker Communication, Organizational Perspective, Personal Feedback, and Relationship with Subordinates. Data were analyzed with Kolmogorov-Smirnov, Shapiro-Wilk and Mann-Whitney U tests and by using other suitable statistical tools. The study reported very low level of communication satisfaction perceived by the junior executives. It also found a significant difference in levels of communication satisfaction between male and female executive in terms of Communication Climate, Personal Feedback and Subordinate Communication. Finally, recommendations were made for developing and maintaining a better organizational communication to achieve the desired performance and to sustain competition in the long run. Journal of Business and Technology (Dhaka) Vol.11(1-2) 2016; 69-90